2010
DOI: 10.4067/s0718-221x2010000300001
|View full text |Cite
|
Sign up to set email alerts
|

Sound Pressure as a Tool in the Assessment of the Surface Roughness on Medium Density Fibreboard Rip Sawing Process

Abstract: This research takes the option of using sound pressure signals to monitor the resulting surface roughness from rip sawing process of medium density fibreboards samples. Different cutting conditions were evaluated, namely cutting speed and feed, giving as a variable the mean chip thickness, being also assessed the effect of the climb cutting and conventional cutting mode. The main results lead to conclude that the sound pressure was closely related to the variation of the mean chip thickness giving adequate lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Because of the need of non-contact measurement, the automatic measurement based on laser imaging was proposed (Hu and Afzal 2005). Aguilera and Barros (2010) suggested to analyze the sound pressure in order to assess and predict the surface roughness. Other authors reported good correlation between results of the contact measurement with stylus and 3D scanning of a wooden surface (Zhong et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the need of non-contact measurement, the automatic measurement based on laser imaging was proposed (Hu and Afzal 2005). Aguilera and Barros (2010) suggested to analyze the sound pressure in order to assess and predict the surface roughness. Other authors reported good correlation between results of the contact measurement with stylus and 3D scanning of a wooden surface (Zhong et al 2013).…”
Section: Introductionmentioning
confidence: 99%